1998
DOI: 10.1037/0097-7403.24.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Priming of attention to local or global levels of visual analysis.

Abstract: Humans can shift attention between parts and wholes, as shown in experiments with complex hierarchical stimuli, such as larger, global letters constructed from smaller, local letters. In these experiments, a target stimulus appears at either the local or the global level, with a distractor at the other level. A shift of attention between levels is said to be demonstrated through a form of priming, whereby targets at one level are presented with a higher probability than at the other level. This base-rate type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 50 publications
3
52
3
Order By: Relevance
“…R. Soc. B 282: 20142384 with other stimuli [47,75,76]. In our case, the reversion to local preference was not purely associative (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…R. Soc. B 282: 20142384 with other stimuli [47,75,76]. In our case, the reversion to local preference was not purely associative (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…More global, lower spatial frequency cues also play a part, as has been shown by Fremouw, Hebranson, and Shimp (1998) and Goto, Wills, and Lea (2004), and this is confirmed by the evidence of some control by head cues in Experiment 1, and by the smooth generalization to morphed stimuli in Experiment 2. It seems clear that the extent to which local-cue domination occurs will depend on the context, as Fremouw et al (1998) and Cook (2001) have argued, and it may even change dynamically (Fremouw, Hebranson, & Shimp, 2002). The present results suggest that an objective analysis of the high and low spatial frequency information actually available in stimuli might help clarify the circumstances under which local domination will be observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that both levels of organization are capable of controlling human and non-human behavior (Cavoto and Cook, 2001;Cook, 1992aCook, ,b, 2001Fremouw et al, 1998Fremouw et al, , 2002Kimchi, 1992), but that humans tend to show precedence for global information over the local information (Navon, 1977(Navon, , 1981Ward, 1982), while pigeons have been shown to give temporal precedence to the local features of such stimuli (Cavoto and Cook, 2001, but see Fremouw et al, 2002).…”
mentioning
confidence: 99%
“…This integrative requirement is of particular importance at the moment because one potential difference that has been identified between human and pigeon perceptual processing concerns how they integrate information and direct attention to the local and global features of hierarchically arranged stimuli (Cavoto and Cook, 2001;Cook, 2001a,b;Fremouw et al, 1998Fremouw et al, , 2002.…”
mentioning
confidence: 99%